The anatomy of the wider benefits of VET in the workplace - (:unkn) unknown (Publications Office of the European Union, 2011)
"This report aims to provide a reference framework to investigate the relationship between training and the wider benefits of learning at the workplace. An empirical analysis, carried out on a representative panel of European households, is combined with the analysis of several case studies. The results confirm indications from organisational psychology literature that employers only obtain the full benefits of the training they provide if training is integrated with a wider set of human resource practices which recognise that employees require - and sometimes expect - some form of continuous development. It is also apparent that continuous development should incorporate not just the acquisition of new skills and competences but also the overall quality of the employee's work situation if the aim is to improve the job satisfaction. The way in which training is integrated with human resource policies to bring about improvements in the work situation of employees has the potential to bring about material improvements for the employer. The message is that there is a need to recognise that improvements to the work situation of the employee are a desirable end in their own right so long as employer gains from training are sustainable." (Hrsg., BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; S 5.3 Personalentwicklung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2 Europa; Betriebliche Weiterbildung; Personalmanagement; Personalentwicklung; Kosten-Nutzen-Analyse; Humankapital; Sozialkapital; Produktivität; Innovationsfähigkeit; Europa